Temporal changes in the implementation of secondary prevention of coronary artery disease in every day practice. (11th May 2021) - Peksa, JW; Jankowski, P; Koziel, P; Bogacki, P; Gomula, P; Mirek-Bryniarska, E; Nessler, J; Podolec, P; Wisniewski, AK; Rajzer, M; Czarnecka, D; Pajak, A
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: - Introduction: Patients with coronary artery disease (CAD) are at high risk of recurrent cardiovascular events and control of their risk factors is crucial. Objectives: Comparison of risk factors control in patients with CAD in 2016–2017 and 2011–2013. Patients and methods: Five hospitals with cardiology departments serving the city and surrounding districts participated in the study. Consecutive patients hospitalized due to an acute coronary syndrome or a myocardial revascularization procedure were interviewed 6–18 months after hospitalization. The surveys were carried out in 2011–2013 and 2016–2017. Results: We examined 616 patients in 2011–2013 and 388 in 2016–2017 (mean age: 64.7 ± 8.8 vs. 66.4 ± 8.4, P <0.01). After adjusting for covariates the proportion of patients with high blood pressure decreased by 8.9% (95% confidence intervals: -2.1% – -15.6%) and proportion of patients with high LDL cholesterol decreased by 9.5% (-2.2% – -16.7%) in 2016/2017 compared to 2011/2013, whereas the proportion of smoking patients (-0.2% [-6.0% – 5.5%]) and those with high glucose level (3.9% [-2.2% - 10.0%]) and with body mass index ≥25 kg/m2 (3.8% [-3.9% – 11.6%]) did not change significantly. The proportion of patients prescribed antiplatelets (6.5% [2.6% - 10.3%]), β-blockers (7.4% [2.2% - 12.6%]), angiotensin converting enzyme inhibitors or sartans (8.6% [2.9% – 14.3%]), calcium antagonists (8.1% [1.3 – 15.0]) and anticoagulants (5.5% [0.7% - 10.2%]) increased significantly. Conclusions: In CAD patients, there was an increase of the proportion of patients with cardiovascular drugs prescribed and a slight improvement in the control of blood pressure and LDL cholesterol between 2011–2013 and 2016–2017. However, no significant changes were found for the other main risk factors.